The effect of royal jelly and propolis alone and in combination on inhibition of Aspergillus parasiticus growth, aflatoxin production, and aflR gene expression. Issue 4 (26th May 2020) - Hamzeh Pour, Siavash; Khodavaisy, Sadegh; Mahmoudi, Shahram; Vaziri, Samira; Soltan Dallal, Mohammad Mehdi; Oliya, Soniya; Getso, Muhammad; Rezaie, Sassan
Abstract: The objective of this study was to determine the inhibitory effect of royal jelly (RJ) and propolis on growth, aflatoxin production and aflR gene expression in Aspergillus parasiticus . Inhibitory effect of RJ and propolis against a standard strain of A. parasiticus (ATCC 15517) was determined alone and in combination in accordance with the CLSI M38‐A2 and checkerboard methods, respectively. The aflatoxin concentrations in the control and treated media were determined by HPLC. Also, the quantitative changes in the aflR gene expression were analyzed. The minimum inhibitory concentrations (MIC) of RJ and propolis alone were 3, 200 and 100μg/ml, respectively. Also, the MICs of RJ and propolis in combination were 200 and 25μg/ml, respectively. When combined, a synergistic interaction was observed with a FICI of 0.312. Total levels of aflatoxin decreased from 386.1ppm to 8.72, 3.01 and 1.75ppm at 1, 600μg/ml of RJ, 50μg/ml of propolis and 100+12.5μg/ml of RJ and propolis, respectively. In addition, the level of afIR gene expression was significantly decreased after treatment with RJ and propolis extracts alone and with their combination. The findings reveal that RJ and propolis extracts, either alone or in combination, have a significant inhibitory effect on aflR gene expression in aflatoxin production. Abstract : Royal jelly (RJ) and propolis were able to inhibit the growth of Aspergillus parasiticus with minimum inhibitory concentrations (MICs) of 3, 200 and 100 μg/ml, respectively. Combination of RJ and propolis resulted in synergistic interaction with MICs of 200 and 25 μg/ml, respectively, and a fractional inhibitory concentration index of 0.312. RJ and propolis were able to down‐regulate the expression of the aflR gene and dramatically decrease the aflatoxin production by A. parasiticus .